The Application of Omnibus Law in Land Regulation Reform Efforts - Rahmad, Agus; Nuraya, Adha; Syam, Fauzi (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
The times provide mandatory demands for laws in Indonesia to develop in accordance with the needs of today's society. However, in reality there are still many rules that intersect with each other and cause legal uncertainty. To deal with this, Indonesian law must be ready to adjust to the renewal of the legal system through omnibus law due to the accumulation of regulations. This research aims to open a new perspective in the implementation of omnibus law on land regulations that have been overlapping, resulting in the absence of legal harmonization. The research method is conducted with a normative juridical approach. The type of approach used is the statute approach. The legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques are carried out by means of literature studies related to research both from laws, scientific works and books. The results of this study indicate that the implementation of the omnibus law is a solution to the overlapping land regulations in Indonesia which must be accompanied by synergy and coordination from various institutions in order to create legal certainty.